Silvae. - Statius, P. Papinius (Mnemosyne, Supplements, 1984)
The five books of the Silvae bring together the occasional verses which Statius wrote in addition to his two epics. In these short descriptive poems Statius elaborates features taken from various genres into an original whole, in which description and eulogy play important roles. The main themes of the poems of his second book are consolation after bereavement and the contrast between nature and culture. The present work contains a general introduction, a text of Silvae II, a bibliography, and an index, together with a verse-by-verse commentary on the poems of this second book. This is the first commentary on a book of the Silvae since Vollmer's commentary on the whole of the Silvae of 1898. Emphasis is here placed on interpretation and moreover chiefly on the literary and stylistic aspects of the poems, which, compared with the epic poetry of Statius and his contemporaries, have hitherto received relatively little attention.